Análise estrutural e teórica de derivados de Chalconas com atividade biológica e propriedades térmicas - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
his study describes the synthesis and structure of (1E,4E)-1-(3-chlorophenyl)-5-(2,6,6-trimethylcyclohex-1-en-1-yl)penta-1,4-dien-3-one (BC I) by X-ray single-crystal diffraction and Hirshfeld Surface (HS) analysis. Theoretical calculations, such as Quantum Theory of Atoms in Molecules (QTAIM), frontier molecular orbital, Molecular Electrostatic Potential (MEP) map and infrared spectra assignments, were performed at the B3LYP/6-311++G(d,p) level of theory. Also, this work evaluates molecular docking against DNA and cytotoxic activity against two tumor cell lines. The BC I molecule has a half chair conformation of the cyclohexene ring, and the supramolecular arrangements are stabilized by C6–H6…O1 and C7–H7…O1 interactions. MEP and docking analyses indicate an electrophilic attack that is likely to occur on the carbonyl group. Besides, three crystal structures (2E,6E)-2,6-bis(4-ethylbenzylidene)cyclohexanone (BH I), (2E,6E)-2,6-bis(2,4-dichlorobenzylidene)cyclohexanone (BH II) and (2E,6E)-2,6-bis(4-chlorobenzylidene)cyclohexanone (BH III) of chalcone based on the cyclohexanone core were synthesized and described by X-ray crystallography and HS analysis. Theoretical calculations using frontier molecular orbital, MEP, hyperconjugative interaction energies, counterpoise procedure, QTAIM and infrared spectra assignments were calculated at ωB97X-D/6-311++G(d,p) level of theory. Besides, the calorific value is determined by the calorimetric pump. The crystal packing for BH I is determined by C3–H3B…O1 interaction and C13–H13B…H13B–C13 dihydrogen contact. Likewise, the crystal packing for BH II is determined by C10–H10A…O1, C20–H20…O1, C17–H17…Cl3 interactions and π…π stacking. Also, for BH III the crystal packing is determined by C6–H6…π, C10–H10B…Cl1 interactions and halogen C1–Cl1…Cl2 contact. The counterpoise procedure was calculated to elucidate the interaction forces that drive the molecular arrangements in the solid-state. Also, hyperconjugative interaction energies and QTAIM analysis were calculated to prove the existence of intermolecular interactions and to classify their nature. Additionally, frontier molecular orbital and MEP were calculated to study their electronic properties and the calorific value analysis revealed that the three compounds have similar calorific capabilities to some fuels.
Keywords: Bischalcona; Bishexanonas; Difração de raios X; Chalconas; Bischalcone; Bishexanones; X-ray diffraction; Chalcone; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::FISICO-QUIMICA